Stenting of Variant Left Carotid Artery Using Brachial Artery Approach in a Patient with Unusual Type of Bovine Aortic Arch - Emre Gürel; Zeki Yüksel Günaydın; Ahmet Karagöz; Osman Bektaş; Adil Bayramoğlu; Abdullah Çelik; Aslı Vural (Case Reports in Cardiology)
Bovine aortic arch is the most frequently encountered variation in human aortic arch branching. A 63-year-old Asian male presented with symptomatic severe stenosis of left carotid artery originating from the brachiocephalic trunk. Selective engagement to the left carotid artery was unsuccessful using transfemoral approach. We reported on a successful left carotid artery stenting case using right brachial artery approach in a bovine aortic arch. This paper is worthy of reporting in terms of guiding physicians for interventional procedures in these types of challenging cases.